Plaster Mould Selection for Ceramic Slip Rotary Moulding System (CSRM) / Norrul Hafizan Ab Wahab ...[et al.] - Ab Wahab, Norrul Hafizan; Saad, Nor Hayati; Nasir, Norazne; Mahamad Sahab, Abdul Rahim (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The suitability of two types of plaster as mould material for CSRM were investigated. The goal of the study is to select the best type of gypsum plaster to be used as mould material for new alternative of ceramic slip casting named as Ceramic Slip Rotary Moulding (CSRM). The new system required porous and stronger mould as complement to the additional system modification of existing conventional ceramic slip casting. Thus, higher lifespan of mould can be produced and directly reducing plaster waste generation. Two(2) types of plaster (hard and soft) were subjected to several test to determine the properties of the plaster in terms of density, particles size, porosity, water absorption and flexural strength. Five(5) samples of each type of plaster were prepared according to ASTM C293-02 for flexural test and ASTM C373-88 for porosity and water absorption test. Result shows that particle size distribution affects the porosity percentage, water absorption and flexural strength of the mould. The larger the particles size the higher the porosity and water absorption percentage of the mould. Soft plaster has the highest porosity level compared to hard plaster. However, when it is exposed to external heat repeatedly, soft plaster reduced its ability to absorb water from time to time. In contradiction, hard plaster gives higher flexural strength compared to soft plaster. In terms of surface roughness, soft plaster produced the most finely green body compared to hard plaster. This result is used as a reference in future research in order to achieve the main goal of producing semi- permanent mould for ceramic slip rotary moulding.